Piezoelectric materials and their applications in radio frequency domain and telecommunications. (12th May 2015) - Benech, P.; Duchamp, J. M.
Abstract : The market of telecommunications has grown rapidly this last decade. The main parameter regarding users is the data rate. It must be increased with each new standard. To reach this goal, the constraints on electronics circuits and devices for radio frequency front end had increased drastically, particularly to obtain high quality radio frequency filters. In this context, piezoelectric materials and devices offer the only way to get radio frequency filters with low insertion losses and high out of band rejection at the same time. A lot of works were performed by several research teams in the world, devoted to materials, to technological steps and to devices. Among piezoelectric materials, some of them are candidates for telecommunications applications. After a review of the main piezoelectric materials, the desired characteristics have been analysed, and finally, few materials are retained. The trends in functionality terms and consequently of required materials for filters are presented for future generations.